Optimization of ether and aniline based inhibitors of lactate dehydrogenase. (1st June 2021) - Christov, Plamen P.; Kim, Kwangho; Jana, Somnath; Romaine, Ian M.; Rai, Ganesha; Mott, Bryan T.; Allweil, Alexander A.; Lamers, Alexander; Brimacombe, Kyle R.; Urban, Daniel J.; Lee, Tobie D.; Hu, Xin; et al.
Graphical abstract: Abstract: Lactate dehydrogenase (LDH) is a critical enzyme in the glycolytic metabolism pathway that is used by many tumor cells. Inhibitors of LDH may be expected to inhibit the metabolic processes in cancer cells and thus selectively delay or inhibit growth in transformed versus normal cells. We have previously disclosed a pyrazole-based series of potent LDH inhibitors with long residence times on the enzyme. Here, we report the elaboration of a new subseries of LDH inhibitors based on those leads. These new compounds potently inhibit both LDHA and LDHB enzymes, and inhibit lactate production in cancer cell lines.